Evaluation of Oral Manifestations of Patients with Parkinson’s Disease–An Observational Study - T. Gopalakrishnan; K.M.K. Mastan; P.E. Chandra Mouli; Naga Leela Guntuku; Priyadharshini A; G. Florence Sangeetha (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Parkinson’s disease is the second most common neurodegenerative disorder which affectsaround four million people globally.Many of the signs of Parkinson’s disease are found in the head andneck. The typical “masklike” facial appearance with infrequent blinking and lack of expression is causedby bradykinesis.. Abnormalities in oral behaviour, such as purposeless chewing, grinding, and suckingmovements, are also well recognized in patients with Parkinson’s disease.Aim and Objectives: The aim of this study is to assess the overall oral health status of the patients withParkinson’s disease and to analyze the impact of Parkinson’s disease on the oral cavity of the individualssurviving with the disease.Materials and Methods: The study sample included 50 Parkinson’s disease patients. The patients of all agegroups and both genders were included.Results: Out of fifty patients. majority of the patient s were above 60 yrs. 6% of the patients reported withPositive family history of Parkinson’s diseases.14% of the patients had gross facial asymmetry, 68% of thepatients showed dryness of mouth.8% of the patients suffered loss of taste.14% of the patients showed hypersalivation. 54% of the patients showed gingivitis. And 76% of the patients were found having periodontitis.Conclusion: Treatment for oral and dental problems of Parkinson’s disease affected patients is mandatory.Treatment can be done by supplementing artificial saliva for dryness of mouth, dental fillings for dentalcaries, periodic scaling for periodontal problems, oral rehabilitation measures and regular dental check up